2024
DOI: 10.1097/ju.0000000000003962
|View full text |Cite
|
Sign up to set email alerts
|

Deep Phenotyping the Anterior Urethral Stricture: Characterizing the Relationship Between Inflammation, Fibrosis, Patient History, and Disease Pathophysiology

Wade R. Gutierrez,
Yi Luo,
Laila Dahmoush
et al.

Abstract: Purpose: Anterior urethral stricture disease (aUSD) is a complex, heterogeneous condition that is idiopathic in origin for most men. This gap in knowledge rarely affects the current management strategy for aUSD, as urethroplasty does not generally consider etiology. However, as we transition towards personalized, minimally invasive treatments for aUSD and begin to consider aUSD prevention strategies, disease pathophysiology will become increasingly important. The purpose of this study was to perform a deep phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In the Trauma and Urologic Reconstruction Network of Surgeons prospective database, the short (L1/L2), proximal/midbulbar (S1a) urethral strictures of idiopathic origin (E2) make up over half of the nearly 3000 strictures in the cohort. 1 While this area is certainly vulnerable DEEP PHENOTYPING THE ANTERIOR URETHRAL STRICTURE…”
Section: Reply By Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Trauma and Urologic Reconstruction Network of Surgeons prospective database, the short (L1/L2), proximal/midbulbar (S1a) urethral strictures of idiopathic origin (E2) make up over half of the nearly 3000 strictures in the cohort. 1 While this area is certainly vulnerable DEEP PHENOTYPING THE ANTERIOR URETHRAL STRICTURE…”
Section: Reply By Authorsmentioning
confidence: 99%
“…This multi-institutional study of urethral stricture etiology aims to identify phenotypic signatures among variable presentations of the disease. 1 Using a combination of patient-reported characteristics, serum inflammatory profiles, and histology, the authors demonstrated an association between clinical etiology and biological profiles. Although all stricture patients had a background elevation in systemic inflammatory markers, the histologic signature of idiopathic strictures resembled that of inflammatory lichen sclerosus more often than traumatic strictures.…”
Section: Editorial Commentmentioning
confidence: 99%